(untitled) (Research, Society and Development, 2020)
The adequate sampling size is an important factor to be taken into account for better accuracy of experiments. Thus, the objective of this paper was to estimate the sample size in the plot necessary to assess the severity of the yellow wheat spot and the area under the disease progress curve (AUDPC). Were used for this study the yellow spot severity and AUDPC of two field trials performed during 2010 wheat crop. The severity of disease was assess in ten leaves per plot, 40 leaves per treatment, after the second spray of fungicide, and from them we calculated the AUDPC. Subsequently, we calculated the following descriptive statistics for each treatment: minimum, maximum, average, standard deviation, variance and coefficient of variation of means. The evaluation of the number of replications and sample size was performed by analysis of variance of each experiment. The dispersal of disease was measured by the variance/means ratio and Morisita index and aimed to verify the methodology used to calculate the sample size was adequate. The dispersion of the disease has not been the same throughout the experiments, varying between treatments and assessment. Given this behavior, the methodology used in this study to calculate the sample size was adequate. For the error of 10%, the sample size to estimate the average severity of the yellow spot and the area under the disease progress curve are 286 and 22 flag leaves, respectively.